2008
DOI: 10.1016/j.mcn.2008.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Altered splicing in exon 8 of the DNA replication factor CIZ1 affects subnuclear distribution and is associated with Alzheimer's disease

Abstract: In order to understand the gene-mediated processes underlying sporadic Alzheimer's disease (AD), we carried out a subtractive cloning screen for novel AD candidate genes. We identified the gene encoding the DNA replication factor CIZ1 (CDKN1A interacting zinc finger protein 1) as being more highly expressed in Alzheimer tissue than in healthy brains. We show here that an isoform of CIZ1 which lacks a glutamine-rich region, due to alternative splicing in exon 8, is upregulated in AD brains relative to the full-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 31 publications
1
41
0
Order By: Relevance
“…In contrast, contact-inhibited normal fetal lung fibroblast MRC5 cells did not resume proliferation or restore CIZ1 -F expression when boosted with serum (Figure 3(e)). This suggests that stable contact-induced growth arrest suppresses expression of CIZ1 -F. In the same MCF-7 cell populations we observed additional effects on CIZ1 alternative splicing, most notably increased CIZ1 -S (Supplementary Figure 3(a)) an isoform reported to be upregulated in Alzheimer’s disease (Supplementary Table 1), and changes in CIZ1 -Δ4 (Supplementary Figure 3(b)) [2,3]. Together the data show that CIZ1-F mRNA and protein are expressed in proliferating cells and inhibited by both serum-deprivation-induced proliferation arrest (MCF-7), and contact-inhibition-induced proliferation arrest (MRC5).…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…In contrast, contact-inhibited normal fetal lung fibroblast MRC5 cells did not resume proliferation or restore CIZ1 -F expression when boosted with serum (Figure 3(e)). This suggests that stable contact-induced growth arrest suppresses expression of CIZ1 -F. In the same MCF-7 cell populations we observed additional effects on CIZ1 alternative splicing, most notably increased CIZ1 -S (Supplementary Figure 3(a)) an isoform reported to be upregulated in Alzheimer’s disease (Supplementary Table 1), and changes in CIZ1 -Δ4 (Supplementary Figure 3(b)) [2,3]. Together the data show that CIZ1-F mRNA and protein are expressed in proliferating cells and inhibited by both serum-deprivation-induced proliferation arrest (MCF-7), and contact-inhibition-induced proliferation arrest (MRC5).…”
Section: Resultsmentioning
confidence: 71%
“…We and others have shown that CIZ1 is a NM protein, defined by its resistance to extraction of chromatin [3,8], which suggests that its function is connected to nuclear architecture, possibly contributing to the spatial regulation of nuclear processes [68,18,24]. Although the NM appears to be corrupted in certain types of cancer [25] previous work [26–28] and our own experiments indicate that MCF-7 cells retain a NM structure to some extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Growing evidence is also indicating that defects in the alternative splicing pathways and generation of wrong alternative variants is a common feature of complex diseases. 88 However, the implications of splice variants in gene networks and how they can affect the metabolism of drugs in patients remains to be explored.…”
Section: Alternative Splicing and Proteome Diversitymentioning
confidence: 99%